(untitled) (Advancements in Homeopathic Research, 2024)
Background: Homeopathy, as a holistic system of medicine, plays a pivotal role in the management of both acute and chronic diseases, offering a potential for permanent cure without causing harm to the patient. This retrospective analysis aims to underscore the advantages of homeopathy, focusing on common chronic ailments such as irritable bowel syndrome (IBS), polycystic ovarian syndrome (PCOD), bronchial asthma, allergic rhinitis, and low backache. Materials and Methods: The study was conducted retrospectively among patients attending the general Outpatient Department (OPD 2) at the National Homeopathy Research Institute in Mental Health, Kottayam, Kerala, every Tuesday from January 2023 to July 2023 (7 months). Analysis of data from 1677 patients revealed patterns of frequently indicated medicines. Results: A total of 1677 patients were included in the study, revealing distinct patterns in demographics and health conditions. The age distribution (Table 1, Figure1) indicated a higher prevalence among individuals aged 51-60 years (24%), while those in the 91-100 age group showed the least representation (1%). Notably, a predominant male presence was observed, constituting 51% of the patient population(Table2, Figure2). Among the patients, 197 were new attendees, while 1480 were returning patients, highlighting the sustained engagement of individuals with homeopathic care over time (Table 3, Figure3). The most prevalent disorders encountered during the study period (Table4, Figure4) were Bronchial Asthma (10%), Acid Peptic Disease (9%), and Diabetes Mellitus (9%). The most frequently used remedies were Sulphur, Pulsatilla, Nuxvomica, and RhusToxicodendron. Conclusion: In summary, this retrospective study involving 1677 patients at the National Homeopathy Research Institute in Mental Health revealed a predominant male demographic, with a concentration of cases in the 51-60 age group. Common disorders included Bronchial Asthma, Acid Peptic Disease, and Diabetes Mellitus, while Sulphur, Pulsatilla, Nuxvomica, and Rhustox emerged as frequently indicated remedies. Notably, the study showcased a remarkable improvement in all patients, affirming the efficacy and significance of homeopathy in achieving positive therapeutic outcomes.